Slightly salinized water enhances the growth and survival of Arapaima gigas larvae - Araújo da Silva, Thyssia Bomfim; Epifânio, Cláudia Maiza Fernandes; Dantas, Francisco de Matos; Rocha, Thayssa Larrana Pinto da; Gonçalves, Ligia Uribe; Dairiki, Jony K. (Aquaculture Research, 2019)
The aim of this study was to evaluate the survival and growth of Arapaima gigas larvae reared in slightly salinized water. Pirarucu larvae (183.1 ± 41.2 mg and 3.4 ± 0.3 cm) were stocked in PVC tanks (20 L; n = 4; 40 larvae per tank) in a static system. A. gigas larvae were reared in increasing levels of salinized water (0, 1, 2, 3 and 4‰) for a period of 15 days. Fish were fed six times a day with Artemia nauplii (2,900 nauplii per larvae per meal in the beginning). The salinized water increased by at least four times the Artemia nauplii lifespan, which prolonged the time of live food supply to Arapaima larvae. Pirarucu larvae kept in freshwater presented the lowest values in weight gain, final weight and survival. Larvae reared in water with 4‰ of salinized water showed the highest final weight. Slightly salinized water enhances the growth and survival of A. gigas larvae and it can be a simple practice with low cost that can be applied in the routine of pirarucu larviculture. © 2019 John Wiley & Sons Ltd
Keywords: Food Supply; Freshwater Ecosystem; Growth; Larva; Larviculture; Length-weight Relationship; Rearing; Salinization; Stocking Density; Survival; Teleost; Arapaima Gigas; Artemia